Determinants of sputum smear non-conversion after intensive phase treatment among pulmonary TB patients in southern Thailand - Buatong, Wilaiwan; Chaimay, Bhunyabhadh; Woradet, Somkiattiyos (The Journal of Infection in Developing Countries, 2026)
Background: Tuberculosis remains a global health challenge, with sputum conversion serving as a critical indicator of treatment success during the intensive phase. This study aimed to identify factors associated with sputum smear non-conversion at the end of intensive phase treatment among patients with pulmonary tuberculosis. Methodology: This case-control study utilized data from the National Tuberculosis Information Program (NTIP) Registry database between 2014 and 2019. Newly diagnosed pulmonary tuberculosis patients were included. The study comprised 322 cases of sputum smear non-conversion and 644 controls who achieved sputum smear conversion. Descriptive statistics and multiple logistic regression were used to analyze the data. Results: Factors significantly associated with sputum smear non-conversion included male sex (Adjusted Odds Ratio [AOR] = 1.57, 95% CI: 1.10-2.25), age 35-59 years (AOR = 1.75, 95% CI: 1.19-2.59), age ≥ 60 years (AOR = 1.72, 95% CI: 1.09-2.71), sputum AFB smear grading of 2+ (AOR = 2.74, 95% CI: 1.20-6.28) and 3+ (AOR = 4.72, 95% CI: 2.14-10.43), and receiving treatment at a private hospital (AOR = 4.94, 95% CI: 2.34-10.44). In contrast, patients weighing ≥ 50 kg at baseline treatment were less likely to experience non-conversion (AOR = 0.72, 95% CI: 0.54-0.96). Conclusions: Patients’ sex, age, sputum acid-fast bacilli [AFB] smear grading, and private hospital access were significant risk factors for sputum smear non-conversion, while higher baseline weight appeared protective. Enhanced monitoring of high-risk groups could improve treatment outcomes.